Impact of abiotic factors on emergence of Avena fatua seeds - Bhuker, Axay; Kaur, Gurvinder; Mor, Virender Singh (Journal of Cereal Research, 2024)
The study was conducted on fresh Avena fatua seeds to assess the effect of abiotic factors specially temperature, light and burial depth on germination during 2023-24. The seeds were exposed to alternating temperatures of 15/20, 20/25 and 25/30°C under two light regimes i.e. 16-hour light/8 hour darkness and continuous darkness for 24 hours. The results revealed that maximum germination (48.66%) was observed at 15/20°C while minimum (27.33%) was recorded at 25/30°C. More germination (37.89%) was observed under complete darkness as compared to 16-hour light/8-hour darkness cycle (33.56%). No hard seeds were found at any temperature and light conditions. Maximum seedling length (20.31 cm), seedling dry weight (7.27 mg), Vigour Index-I (992.80), Vigour Index-II (355.69) and radicle emergence (46.42%) were observed at 15/20°C whereas minimum seedling length (15.22 cm), seedling dry weight (6.17 mg), Vigour Index-I (484.40) and Vigour Index-II (169.19) were observed at 25/30°C. Between the light regimes, more seedling length (19.06 cm), seedling dry weight (7.06 mg), vigour index-I (747.18), vigour index-II (272.74) and radicle emergence (35.53%) were recorded under complete darkness as compared to 16-hour light/8-hours darkness cycle where seedling length (14.64 cm), seedling dry weight (6.35 mg), Vigour Index-I (569.13), Vigour Index-II (215.67) and radicle emergence (26.63) were recorded less. Field emergence and speed of germination were reduced as the burial depth increased and maximum field emergence (33.67%) and speed of emergence (4.94) were recorded at 4 cm and minimum field emergence (29.33%) and speed of emergence (3.62) at 8 cm depth. The information will be helpful for the effective management of objectionable weed wild oat.